HANDLING OF UNLIVABLE HOUSES IN COASTAL SLUM AREAS OF BATU BARA DISTRICT - Lendi Aprianto; Abdi Sugianto; Cut Nuraini (PT. Radja Intercontinental Publishing, 2025)
This study aims to explore the management of uninhabitable housing in coastal slum areas of Batu Bara Regency. The main focus of this study is to identify the factors causing the high number of uninhabitable housing and the efforts that have been made by the local government and community to address it. The research findings indicate that the main obstacles in managing uninhabitable housing are budget constraints, land ownership issues, and low community participation. Furthermore, existing government assistance programs are still insufficient to cover all homes in need of repair. This study proposes several strategies to improve the effectiveness of uninhabitable housing management, including increasing the budget, empowering communities, and improving coordination between the government, the private sector, and the community. With a more holistic and coordinated approach, it is hoped that the condition of uninhabitable housing in coastal slum areas of Batu Bara Regency can be improved sustainably.